GE_GERICHTE P/10656/2018 vom 18. November 2020 - GE Cour de justice (2020)
SEQUESTRATION;LÉSION CORPORELLE SIMPLE;MENACE(DROIT PÉNAL);VIOL;TENTATIVE(DROIT PÉNAL);EXPULSION(DROIT PÉNAL) | CP.183; CP.123; CP.180; CP.190; CP.22.al1; CP.66